The Moderating Effect of Capital Structure on the nexus between Price Earning Ratio, Size, Profitability, and Company Value - Widiastuti Widiastuti; Purwanti Purwanti; Elsye Fatmawati (ProBisnis : Jurnal Manajemen, 2023)
The researcher investigates the impact of price-earning ratio, size, and profitability on company value and the capital structure moderating those effects in publicly listed SOE enterprises on the Indonesia Stock Exchange (IDX) in 2018–2021. Quantitative research. This study used secondary data. This study used purposive and non-probability sampling to select 12 companies for 48 observations. The data analysis methods used in this study are descriptive statistical analysis, panel data regression analysis, classical assumption test, t-test, and Moderate Regression Analysis (MRA) utilizing the Eviews 12 application. The IDX website (www.idx.co.id) documents data collecting. This study found that company value is unaffected by the price-earning ratio and profitability. Size negatively affects company value. Price-earning ratio, size, and profitability affect company value regardless of capital structure.